Post-rift volcanic structures of the Pernambuco Plateau, northeastern Brazil. (October 2016) - Buarque, Bruno V.; Barbosa, José A.; Magalhães, José R.G.; Cruz Oliveira, Jefferson T.; Filho, Osvaldo J. Correia
Abstract: The Pernambuco marginal basin is located on the eastern continental margin of northeastern Brazil, covers an area of 20, 800 km 2, and represents one of the most prominent frontiers for deep water oil and gas exploration off the Brazilian coast. The onshore region of this basin was highly affected by extrusive and intrusive magmatism during the Upper Albian, and the relation of that event with the volcanic structures observed in the offshore sector has not been thoroughly characterized to date. This study aims to characterize the major extrusive and intrusive volcanic structures of the offshore portion of this basin, which is dominated by the Pernambuco Plateau, and its stratigraphic relations. A set of 143 2D multichannel seismic sections that cover the Pernambuco Plateau region are used to interpret the major tectono-stratigraphic sequences and describe the distribution of volcanoes, sills, vent complexes and related volcaniclastic sequences. The interpretations are supported by aeromagnetic and gravimetric geophysical surveys. Volcanoes are classified into two groups that differ in terms of their morphology: shield-like structures and cone-shaped volcanic structures. Sill intrusions are mainly identified beneath the volcanic structures and are characterized by high-amplitude reflectors with short extensions and abrupt terminations. Volcaniclastic sequences are found adjacent to the volcanoes and are characterized by high-amplitude, disrupted reflections with local chaotic configurations. Vent complexes are classified on the basis of their morphologies as either eye-shaped or crater-shaped. The volcanic features identified within the available seismic dataset are concentrated in two main areas: in the centre of the plateau and near its northeastern border. These two regions are host basement outer highs and are surrounded by hyper-extended continental crust, which forms the plateau itself. The extrusive and intrusive features described in the offshore region were formed during the post rift Cretaceous and Cenozoic intervals and point to the continuation of magmatic events after the rifting process. The findings presented in this report provide a better understanding of the magmatism on the northeastern passive margin of Brazil and can also be useful for future modelling of the Pernambuco Basin petroleum system. Highlights: Different types of volcanic structures were identified in the Pernambuco Basin. Sill intrusion reflectors had limited extension and abrupt terminations. Vent complexes had crater and eye-shaped geometries. Magnetic anomalies trending NW-SE associated with magmatic processes were observed.